2022
DOI: 10.1155/2022/4108231
|View full text |Cite|
|
Sign up to set email alerts
|

Enhancing Vehicular Ad Hoc Networks’ Dynamic Behavior by Integrating Game Theory and Machine Learning Techniques for Reliable and Stable Routing

Abstract: VANETs (vehicular ad hoc networks) have evolved as a platform for enabling intelligent inter-vehicle communication while also improving traffic safety and performance. VANETs are a difficult research topic because of the road dynamics, high mobility of cars, their unlimited power supply, and the growth of roadside wireless infrastructures. In wireless networks, game theory approaches have been widely used to investigate the interactions between competitive and cooperative behavior. In this research, we propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The simulation gives the provision to choose sender, receiver, intermediate nodes and their communication technology. Ambulances are chosen as the sender for this simulation study along with a VANET-based telemedicine architecture, with IEEE 802.11 as the radio access technology (RAT) [54][55][56]. The mobile ambulances are simulated to traverse through different types of traffic scenarios experienced in rural, suburban, and urban areas, totalling a 6km road stretch.…”
Section: Simulation Scenariosmentioning
confidence: 99%
“…The simulation gives the provision to choose sender, receiver, intermediate nodes and their communication technology. Ambulances are chosen as the sender for this simulation study along with a VANET-based telemedicine architecture, with IEEE 802.11 as the radio access technology (RAT) [54][55][56]. The mobile ambulances are simulated to traverse through different types of traffic scenarios experienced in rural, suburban, and urban areas, totalling a 6km road stretch.…”
Section: Simulation Scenariosmentioning
confidence: 99%
“…In [23], they focus on the use of machine learning in Vanet, particularly in its applicability to security and communication networks. A methodology for vehicular machine learning is presented, and various models and systematic techniques are reviewed.…”
Section: Machine Learningmentioning
confidence: 99%
“…It has been shown that most accidents can be avoided by warning drivers one half second in advance [ 4 ]. Vehicular ad hoc networks (VANETs) have been developed recently to reduce accidents, improve traffic efficiency and road safety, and enhance user comfort [ 5 ]. VANETs enable vehicles to communicate with other vehicles via Vehicle-to-Vehicle (V2V) communication, and to communicate with roadside units (RSUs) via Vehicle-to-Infrastructure (V2I) communication, to exchange information and inform drivers about road hazards.…”
Section: Introductionmentioning
confidence: 99%